PHARMACOGENOMIC CONSIDERATIONS FOR PRESCRIBING THE ANTIDEPRESSANT FLUOXETINE: A REVIEW IN PERSONALIZED MEDICINE - Karimi, Isaac; Yakhchalian, Nima; Fathi, Mazyar; Miraghaee, Seyed Shahram (Universal Journal of Pharmaceutical Research, 2022)
The worthwhile intellectual synthesis proposing that nothing makes sense except in light of context has also revolutionized pharmaceutical science putting patients’ genomic context at the center of attention in a rapidly developing area known as pharmacogenomics. As a result, an alternative approach to medicine referred to as personalized medicine was born considering the individual-specific genomic context the hardcore of any diagnostic, prognostic, and therapeutic intervention. Therefore, a considerable need has been created to address questions based on the underlying genotypic characteristics of patients. Depressive spectrum disorders are a cluster of closely-linked psychiatric disorders with a growing incidence rate across the world. Although there are multiple therapeutic approaches to treating depressive spectrum disorders, pharmacotherapy is still considered one of the most effective strategies. Among the therapeutic antidepressant drugs, selective serotonin reuptake inhibitors (SSRIs) are most widely prescribed. Fluoxetine (FLX) is a highly valued SSRI which is broadly ordered by psychiatric practitioners to treat miscellaneous psychological disorders, including depressive spectrum disorders, anxiety spectrum disorders, and obsessive-compulsive disorder. Although FLX therapy can bring about a positive therapeutic effect on a considerable proportion of depressed patients, it does not elicit a favorable response in 30-40% of patients owing to the presence of genomic variations negatively affecting the pharmacokinetic and pharmacodynamic characteristics of this medication. This challenging fact has led us to conduct current research on how genotypic variations at the inter-individual level can heavily affect the response to FLX therapy. Peer Review History: Received: 7 April 2022; Revised: 12 May; Accepted: 13 June; Available online: 15 July 2022 Academic Editor: Dr. Amany Mohamed Alboghdadly , Princess Nourah bint abdulrahman university, Riyadh, amalbgadley@pnu.edu.sa Reviewers: Prof. Dr. Hassan A.H. Al-Shamahy, Sana’a University, Yemen, shmahe@yemen.net.ye Dr. George Zhu, Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com